Chloroplast Phylogenomic Analyses Reveal a Maternal Hybridization Event Leading to the Formation of Cultivated Peanuts - Tian, Xiangyu; Shi, Luye; Guo, Jia; Fu, Liuyang; Du, Pei; Huang, Bingyan; Wu, Yue; Zhang, Xinyou; Wang, Zhenlong (Frontiers in Plant Science, 2021)
Peanuts (Arachis hypogaea L.) offer numerous healthy benefits, and the production of peanuts has a prominent role in global food security. As a result, it is in the interest of society to improve the productivity and quality of peanuts with transgenic means. However, the lack of a robust phylogeny of cultivated and wild peanut species has limited the utilization of genetic resources in peanut molecular breeding. In this study, a total of 33 complete peanut plastomes were sequenced, analyzed and used for phylogenetic analyses. Our results suggest that sect. Arachis can be subdivided into two lineages. All the cultivated species are contained in Lineage I with AABB and AA are the two predominant genome types present, while species in Lineage II possess diverse genome types, including BB, KK, GG, etc. Phylogenetic studies also indicate that all allotetraploid cultivated peanut species have been derived from a possible maternal hybridization event with one of the diploid A. duranensis accessions being a potential AA sub-genome ancestor. In addition, A. monticola, a tetraploid wild species, is placed in the same group with all the cultivated peanuts, and it may represent a transitional species, which has been through the recent hybridization event. This research could facilitate a better understanding of the taxonomic status of various Arachis species/accessions and the evolutionary relationship among them, and assists in the correct and efficient use of germplasm resources in breeding efforts to improve peanuts for the benefit of human beings.